The Newspapers in the Social Networks: Hearings, Content, Interactivity and Commercial Strategies - Túñez López, Miguel (Estudios sobre el Mensaje Periodístico, 2012)
The social networks have been consolidated, with million users, as a support of communication and a channel of informative flows in which the interpersonal relations coexist with strategies organizational of all kinds. This article analyzes the activity and the contents of 23 diaries (general, economic, sports and free) of major issue in three social networks with more followers in Spain (Facebook, Twitter and Tuenti), attending principally to four parameters: interactivity; making and presentation of contents; hearings and followers; and commercial strategies.